Review Of The Fund's Income Position For FY 2020 And FY 2021-2022. (Policy Papers; Policy Paper, 2020)
This paper reviews the Fund's income position for FY 2020 and FY 2021-22. It updates the April 2019 projections and proposes decisions for the current year. The paper also includes a proposed decision to set the margin for the rate of charge for financial years 2021 and 2022. Projections of the Fund's income are subject to larger than normal uncertainties related to the impact of the COVID-19 pandemic on key assumptions. For FY 2020, these uncertainties relate mainly to the discount rate used to measure the Fund's retirement plan obligations at April 30, 2020 and to the full year asset returns on the retirement plan and the Endowment Subaccount (EA), given the recent volatility in financial markets. For FY 2021-22, a key additional uncertainty is the scale of new lending associated with the economic fallout from the COVID-19 pandemic.